2014
DOI: 10.1080/08111146.2014.883967
|View full text |Cite
|
Sign up to set email alerts
|

Inter-ethnic Partnerships: Remaking Urban Ethnic Diversity

Abstract: Inter-ethnic couples are a growing population with unique and understudied residential geographies. Using customised 2006 Census data for the Greater Sydney region, we investigate the prevalence and geographic distribution of a socially significant subset of cohabiting inter-ethnic couples: ethnic majority-minority couples. These couples are comprised of an Anglo/European or ('white') Australian partner and a partner from a 'visible' ethnic minority group. We find that ethnic majority-minority couples are most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…In Australia, Walker and Heard (2014) and Biddle (2013) found that Indigenous persons with non-Indigenous partners tend to live in urban areas, which typically have lower proportions of Indigenous residents. Our research in Sydney (Tindale et al, 2014) demonstrated that ethnic minority persons with ethnic majority partners were considerably less likely (than their co-ethnically partnered peers) to live in neighbourhoods with a high presence of same-ethnicity residents. Dispersal was also evident amongst ethnic majority persons: those with an ethnic minority partner were much less likely to live in predominantly 'white' parts of Sydney.…”
Section: Residential Dispersal and Neighbourhood Diversitymentioning
confidence: 66%
See 2 more Smart Citations
“…In Australia, Walker and Heard (2014) and Biddle (2013) found that Indigenous persons with non-Indigenous partners tend to live in urban areas, which typically have lower proportions of Indigenous residents. Our research in Sydney (Tindale et al, 2014) demonstrated that ethnic minority persons with ethnic majority partners were considerably less likely (than their co-ethnically partnered peers) to live in neighbourhoods with a high presence of same-ethnicity residents. Dispersal was also evident amongst ethnic majority persons: those with an ethnic minority partner were much less likely to live in predominantly 'white' parts of Sydney.…”
Section: Residential Dispersal and Neighbourhood Diversitymentioning
confidence: 66%
“…These couples occupied an 'in-between' space in the ethno-racial landscape of cities, not aligned with existing racial geographies (Holloway et al, 2005;Wright et al, 2011). Lending support to Holloway et al's (2005) 'in-between' thesis, Tindale et al (2014) showed that mixed-ethnicity couples in Sydney live in more diverse areas than co-ethnic majority couples, but less diverse areas than co-ethnic minority couples.…”
Section: Residential Dispersal and Neighbourhood Diversitymentioning
confidence: 92%
See 1 more Smart Citation
“…There is an emerging interest amongst Australian and British geographers in interethnic relationships. For example, Tindale et al () explored the geography of interethnic couples in Sydney, Australia, noting that experiences of racism or the expectation that racism would be experienced in particular places likely influenced residential choices. Klocker () compared growing ethnic diversity within Australian family life with portrayals of interethnic couples on television, noting that portrayals of committed interethnic intimate relationships were few and far between (see also Klocker and Stanes, ).…”
Section: Racism and Familiesmentioning
confidence: 99%
“…Affordable transportation and telecommunication allows immigrants to become increasingly transnational, keeping in touch with their homeland while successfully adjusting in the host nation (Iarmolenko, Titzmann, & Silbereisen, ; Leyendecker, ; Portes, Guarnizo, & Landolt, ). At the same time, interethnic partnerships are on the rise (Tindale, Klocker, & Gibson, ; Wright, Ellis, & Holloway, ) and, as one paper in this special section shows, transracial adoptions are gaining in prevalence (Ferrari, Ranieri, Barni, & Rosnati, ). In sum, more and more individuals are confronted with several cultures, even though they do not necessarily have a first‐hand migration experience.…”
mentioning
confidence: 99%